Santa Eulalia de Bóveda (Lugo): ensayo sobre la cronología de las pinturas - Carrocera Fernández, Elias (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2017)
The trial, from reading and reviewing pictorial cycles, proposes two different chronologies that justify two different cultural stages: one related to the Late Antiquity and another with the High Middle Age. Moreover, the use of pictorial scenery created justifying different ideological assumptions discussed.